Nationalism, democracy and national integration in China - Liew, Leong H.; Wang, Shaoguang, 1954- (RoutledgeCurzon contemporary China series, 2004)
This book examines the changing role of nationalism in China in the light of the immense political and economic changes there during the 1990s.